Do planting methods and nitrogen management interfere with the economic viability of the melon crop? - Vendruscolo, Eduardo Pradi; Bortolheiro, Fernanda Pacheco de Almeida Prado; Martins, Murilo Battistuzzi; Campos, Luiz Fernandes Cardoso; Seleguini, Alexsander; de Lima, Sebastião Ferreira (Comunicata Scientiae, 2020)
Proper crop management results in higher profitability and the verification of economic viability is paramount to the definition of the methodologies used. This study aimed to verify the economic viability of seedlings or seeds use, associated with the inoculation with Azospirillum brasilense and nitrogen in topdressing fertilization in Cantaloupe melon production. The experiment was designed in randomized blocks with eight treatments. The treatments were composed of planting methods (seedling or seed), inoculation with Azospirillum brasilense (with or without), and partial application of 120 kg ha-1 of nitrogen as topdressing fertilization (with and without). It was verified that operations and seed acquisition represent the major cost factors. As for treatments, the use of seedling transplants with topdressing fertilization with nitrogen results in an increase of up to 37.01% in fruit production and, consequently, increases the indicators of economic viability. Also, A. brasilense, although not resulting in significantly higher production, raises the profitability. In this way, the seedling transplant, combined with the nitrogen in topdressing fertilization, results in higher profitability, and the use of A. brasilense is a technique with the potential for use in melon cultivation.